Supporting parents with disability and other challenges through occupational therapy: what is needed? - Honey, Anne; Almomani, Fidaa; Chen, Yu‐Wei Ryan; Codd, Yvonne; Kim, Junghun A. J.; Kunishige, Masafumi; Morrison, Rodolfo; Mara, Veronica O.; Peterson, Jessica; Pituch, Evelina; Rider, John V.; Romli, Muhammad Hibatullah; et al. (John Wiley and Sons Inc, 2025)
Introduction: Parenting is a highly valued and challenging occupational role in which many parents experience challenges. Yet the involvement of occupational therapy in supporting parenting for adults with disability and other challenges is relatively low. This paper explores what is needed to increase occupational therapy support for parents with disability and other challenges. Methods: An international online survey was developed based on previous literature and refined via cognitive interviews. It was reviewed by international occupational therapy academics from 11 countries and translated into eight languages. The survey sought the experiences and views of occupational therapists who work with adult populations about supporting parenting occupations. For this paper, fixed-choice and free-text responses illuminating what is needed to increase the provision of that support were analysed. A mixed methods design was used, combining descriptive statistics and interpretive content analysis. Multivariate multinominal logistic regression analyses were used to assess associations between needs identified and participant and practice characteristics. Consumer and Community Involvement: This survey and paper were developed with input from occupational therapists and occupational therapy academics from 13 countries. Results: Participants (n = 1347) identified six types of factors needed to increase occupational therapy support for parenting occupations in adult populations. These were supportive institutional structures; training, resources and assessments; and recognition of occupational therapists' suitability to support parenting both within and outside the profession. Responses varied somewhat by country, setting, population, previous training and clinical experience. Conclusion: Increasing occupational therapy support for parents with a variety of disabilities and other challenges requires efforts from individual occupational therapists, professional bodies, organisations and educators.